Improving Poetry Appreciation Ability Through Demonstration Methods in Indonesian Language Students - Cahyo Prawoto, Eko; Pana Pramulia; Nur Rohmah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literature teaching has a very important role in providing knowledge about life and fostering emotional sensitivity in students. Therefore, to create literature teaching that is in line with its objectives, Indonesian language teachers are needed who have adequate competence in appreciating literary works. This can be done through the presentation of literary learning in lecture rooms. However, in reality there are problems faced by students in appreciating poetry. For this reason, further efforts are needed to overcome this problem by applying demonstration methods. This research focuses on efforts to increase students' ability to appreciate poetry through demonstration methods. The research method used in this research is a descriptive qualitative method with an experimental approach. The subjects of this research were 24 class A students of the Indonesian Language Education study program class A. The result of the research carried out is the implementation of the demonstration method as an effort to increase student competence in appreciating poetry that works well, as well as achieving learning objectives. Because there was an increase in the average score obtained by students from 2.75 to 4.26 which is included in the good category.